Mudas de cana-de-açúcar influenciadas pelo manejo com herbicidas - Silva, T. P. (2018)
This research aimed at studying herbicides selectivity on individuals from three sugarcane families after different chemical managements in primary selection fields (F1). On the field, a randomized block design with five replications in a split plot scheme was used. Twelve herbicide treatments were allocated in the plots and the three seedlings families were allocated in the sub-plots. The herbicides treatments were T1– tebuthiuron POST-i+ ametryn POST-t; T2– (diuron + hexazinone) POST-i+ ametryn POST-t; T3– sulfentrazone POST-i+ ametryn POST-t; T4– (diuron + hexazinone) POST-i+ metribuzin POST-t; T5– sulfentrazone POST-i+ metribuzin POST-t; T6– imazapyr IPP; T7– imazapyr IPP + ametryn POST-t; T8– imazapyr IPP + metribuzin POST-t; T9– imazapyr IPP + tebuthiuron POST-i; T10– imazapyr PPI + (diuron + hexazinone) POST-i; T11– imazapyr IPP + sulfentrazone POST-iand T12- weeded control. Families were F400 (♀IAC086155 x ♂?), F43 (♀IACBIO264 x ♂IAC911099) and F14 (♀IACSP991305 x ♂GlagaH). For each individual, the intoxication symptoms and the chlorophyll content on the leaves (40 and 120 DAApós-i), the percentage of live seedlings and selected seedlings (240 DAApós-i) were evauated. The chemical management with alternative treatments (T2 to T11) was selective to the three seedlings families because it caused slight intoxication symptoms and interference in the chlorophyll content, in addition to the high percentage of survival that allowed the plants selection for the later stage (F2). The management with herbicide applied in incorporated pre-planting (IPP) was highlighted as selective even when supplemented after the establishment phase of seedlings (POST-t).